Influence of Alkali Metal Ions on the Structural and Spectroscopic Properties of Sm3+-Doped Silicate Glasses - Montoya Matos, Israel Roger (2023)
In the present work, the influence of alkali ions (Li, Na, K) on the structural and spectroscopic properties of silica glasses doped with Sm3+ was investigated. Infrared and Raman spectroscopy techniques were used to investigate the structural properties of the alkali silicate glasses. The optical absorption showed bands characteristic of Sm3+ ions in alkali silicate glasses, and this was investigated. The Judd–Ofelt theory was applied to evaluate the phenomenological intensity parameters (O2, O4, and O6) of the optical absorption measurements. The multi-channel visible and near infrared emission transitions originating from the 4G5/2-emitting state of the Sm3+ in alkali silicate glasses with a maximum phonon energy of ~1050 cm-1 were investigated. From the evaluated Judd–Ofelt parameters, radiative parameters such as spontaneous emission probabilities, radiative lifetimes, branching ratios, and stimulated emission cross-sections were calculated. The recorded luminescence spectra regions revealed intense green, orange, red, and near-infrared emission bands, providing new traces for developing tunable laser and optoelectronic devices.